Factors influencing air transport rates and fares - FitzGerald, Garret (Statistical and Social Inquiry Society of Ireland, 1952)
Three primary choices face every transport operator: the choice of his field of operations, of a vehicle or vehicles suitable for this field, and of a rate structure that will ensure the maximum return on his activities. A secondary choice is that of the schedule to be operated i.e., the practical application of the vehicle to the field of operations at the fare structure in force at any time. This is the scope of transport economics.
Read before the Society, 28 March 1952
Keywords: Air transport rates; Air transport fares; Irish aviation sector; Transport economics; Aviation, Ireland; 314.15